Effect of 17α-methyl testosterone on sex reversal and growth performance of Nile tilapia,Oreochromis niloticus - Belete Berhanu; Kassaye BalkewWorkagegn; Natarajan Pavanasam (East African Journal of Biophysical and Computational Sciences)
The present study aimed at developing all-male Nile tilapia using17α-methyl testosterone(17α-MT) along with its growth and feed utilization performances. Three days old Niletilapia fry were stocked in plastic jars with 5 L capacity installed in four fiber glass tanks. The fry were fed with 0, 30, 60, and 100 mg MT/kg diets for 30 days. Later, the fry were shifted to hapas installed in a pond and then, reared for four months separately. The fish were fed with the control diet. The results showed that the highest male population(93.6%) was observed in the fish treated with a 60 mg MT/kg diet, while the lowest(82.6%) was observed in the fish treated with a 30 mg MT/kg diet. The results also showed that the fish fed with a 60 mg MT/kg diet had significantly higher mean body weight (24.1±1.40 g), specific growth rate (2.5±0.10%), feed conversion ratio (1.3±0.10), and protein efficiency ratio (0.63±0.11) than the untreated fish treated (control) group. In conclusion, a 60 mg MT/kg diet can be considered as an optimal and economically viable dose for Nile tilapia sex reversal along with its optimum growth and feed utilization performances.